Pooling biodiversity offsets to improve habitat connectivity and species conservation. (1st January 2021) - Tarabon, Simon; Dutoit, Thierry; Isselin-Nondedeu, Francis
Abstract: Land developers can apply biodiversity offsetting in different ways, from a project-by-project approach to a pooled and proactive approach, this latter appearing to provide greater advantages both in terms of implementation and of the No Net Loss objective. Incorporating landscape connectivity into the mitigation hierarchy is commonly recommended, but the benefits of pooling and anticipating offsets have never really been demonstrated from modeling approaches. Here, we compare connectivity gains from two different offsetting scenarios, when interconnections at offset sites are taken and not taken into account. Assuming that gains can be increased by optimizing the location of offsets, we identified sites where biodiversity offsetting generates the greatest ecological gains in habitat connectivity. The method was applied to a study case in the suburbs of Lyon (Southern France) using several representative species and the landscape functional connectivity model Graphab . Pooling biodiversity offsets led to additional gains in overall habitat connectivity of +103% on average, which we show can be further improved (+8%) by using a patch addition process available in Graphab to plan spatially and ecologically coherent offsetting areas. Pooling and anticipating biodiversity offsets in this way can help preserve the biodiversity and the functionality of natural environments at the territorial scale. Highlights: Modeling can be used to simulate different biodiversity offsetting strategies. Biodiversity is improved by pooling biodiversity offsets in landscapes. Pooling biodiversity offsets improves the likelihood of achieving no net loss.